Primary hyperaldosteronism is associated with increased mortality and morbidity in patients with hypertension and diabetes - Pillai, Krishnadev; Fares, Ahmed; Dargham, Soha; Al Suwaidi, Jassim; Jayyousi, Amin; Abi Khalil, Charbel (Frontiers in Endocrinology, 2023)
Aims: Primary hyperaldosteronism (PA) is a common cause of hypertension. It is more prevalent in patients with diabetes. We assessed the cardiovascular impact of PA in patients with established hypertension and diabetes. Methods: Data from the National Inpatient Sample (2008-2016) was used to identify adults with PA with hypertension and diabetes comorbidities and then compared to non-PA patients. The primary outcome was in-hospital death. Secondary outcomes included ischemic stroke, hemorrhagic stroke, acute renal failure, atrial fibrillation, and acute heart failure. Results: A total of 48,434,503 patients with hypertension and diabetes were included in the analysis, of whom 12,850 (0.03%) were diagnosed with primary hyperaldosteronism (PA). Compared to patients with hypertension and diabetes but no PA, those with PA were more likely to be younger [63(13) vs. 67 (14), male (57.1% vs. 48.3%), and African-Americans (32% vs. 18.5%) (p<0.001 for all). PA was associated with a higher risk of mortality (adjusted OR 1.076 [1.076-1.077]), ischemic stroke [adjusted OR 1.049 (1.049-1.05)], hemorrhagic stroke [adjusted OR 1.05 (1.05-1.051)], acute renal failure [adjusted OR 1.058 (1.058-1.058)], acute heart failure [OR 1.104 (1.104-1.104)], and atrial fibrillation [adjusted OR 1.034 (1.033-1.034)]. As expected, older age and underlying cardiovascular disease were the strongest predictors of mortality. However, the female gender conferred protection [OR 0.889 (0.886-0.892]. Conclusion: Primary hyperaldosteronism in patients with hypertension and diabetes is associated with increased mortality and morbidity